Treasury Management Training For Bank of China Employees - Tanti Widia Nurdiani (CV. Ulil Albab Corp, 2022)
Over the last several decades, corporate treasury management methods have evolved significantly. Treasury management's duties continue to expand. The Bank of China, which has been commercially active in Indonesia since 1938, is one of the international banks that has begun to recognize the importance of treasury management. As a management organization, Smart Indonesia Academy offers treasury management training to the Bank of China team as a means of empowering the community. The goal of this research was to conduct an analysis of the Smart Indonesia Academy program, which included delivering marketing training for treasury management to the Bank of China team in the context of community empowerment. This is a qualitative study using an analytical descriptive strategy. The findings indicated that the community service on March 30, 2022, was conducted efficiently and successfully. Additionally, the Bank of China team believes that similar community service initiatives may be sustained with a variety of different subjects or issues.